‘DEEDS RECORDATION’ ‘TITLE REGISTRATION’. ROZWIąZANIA MODELOWE W ZAKRESIE REJESTRóW NIERUCHOMOŚCI W SYSTEMIE ‘COMMON LAW’ - Blajer, Paweł (Zeszyty Prawnicze, 2016)
DEEDS REGISTRATION AND TITLE REGISTRATION: MODEL SOLUTIONS CONCERNING LAND REGISTRIES IN THE COMMON LAW SYSTEM Summary The aim of this article is to present the two main land registration models in the common law countries, i.e. deeds recordation and title registration, taking into account the broader historical perspective indicating their origins, evolution and developments, as well as the current state of legal regulations in the field of registration of interest in land. The system of deeds recordation is characterized on the basis of regulations adopted in the vast majority of the US states, whereas the title registration model is presented against the background of the Torrens system, the origins of which date back to 19th-century Australian legislation. From Australia this particular land registration system spread to other continents. A comparison is carried out of the two systems, taking into account their advantages and disadvantages, and the reasons for the global success of the title registration model are indicated. On the grounds of the regulations adopted in Scotland and the Republic of South Africa the author makes also an attempt to characterize the mixed systems, which are generally based on the deeds recordation model but emploi some solutions typical for the title registration system. Concluding the article, the author tries to indicate the particular characteristics of title registration model which could be a source of inspiration for the potential optimization of the Polish land registry system.